The importance of digital playful games for the teaching and learning process: A qualitative study - Santos, José Leonardo Diniz de Melo; Lopes , Aline Costa; Talbot, Teddy; Rodrigues, Riverson Ferreira; Souza, Indiria Tibolla Alexandre de; Mello , Elizeu Crispim de; Moraes, Paulo Sérgio de; Duarte, Lucio Andrade; Duarte, Maria Josany da Costa; Albuquerque , Thatiane Fernandes Cabral de; Herculano, Diêgo Cabral; Morais, Sérgio David de; et al. (Seven Editora, 2024)
This research aimed to analyze teachers' perceptions about the importance of digital playful games in the teaching and learning process. Using a qualitative approach, the research was conducted through in-depth interviews with fifteen teachers from a Brazilian public school. The interviews were recorded, transcribed and analyzed using the discourse analysis technique. The results revealed that teachers recognize the potential of digital playful games to promote student engagement, making classes more dynamic and attractive. Games were identified as facilitators for the exploration and understanding of complex concepts, in addition to stimulating cognitive and socio-emotional skills, such as critical thinking and collaboration among students. However, challenges related to specific teacher training and adequate school infrastructure were identified. Digital playful games have been found to be effective pedagogical tools to improve the quality of teaching and learning, promoting the holistic development of students. However, it is necessary to address the challenges associated with its implementation to maximize the benefits and minimize the negative impacts. DOI:https://doi.org/10.56238/sevened2024.009-005